2018 Changes to the Evidence Act and Criminal Procedure Code - The Criminal Justice Reform Bill and Evidence (Amendment) Bill - CHEN, Siyuan (Institutional Knowledge at Singapore Management University, 2018)
Various portions of the Evidence Act and Criminal Procedure Code were amended in 2018 vide the Criminal Justice Reform Bill and Evidence (Amendment) Bill; this was a continuation of a series of gradual but important changes to the criminal justice system that had begun in 2010 when the old Criminal Procedure Code was replaced. This legislation comment outlines and briefly analyses some of the most substantive changes brought about by the 2018 amendments: the video-recording of interviews in criminal proceedings; the introduction of a psychiatrist panel to regulate the reception of evidence from expert psychiatric witnesses in criminal proceedings; and the use of deferred prosecution agreements for certain corporate offenders.